Control of Cracking in Reinforced Concrete Structures. (2016) - Barre, Francis; Bisch, Philippe; Chauvel, Daniele; Cortade, Jacques; Coste, Jean-François; Dubois, Jean-Philippe; Erlicher, Silvano; Gallitre, Etienne; Mazars, Jacky; Rospar, Claude; Sellier, Alain; Torrenti, Jean-Michel; et al.
No abstract available